Improving concrete quality - Obla, Karthikeyan H. (CRC Press, Taylor & Francis Group, 2015)
Quality measurement is not prevalent in the concrete industry and quality investment is not seen as potentially generating a positive return. Improving Concrete Quality examines how and why concrete quality should be measured, and includes instruction on developing specifications with the aim of improving concrete quality